The effects of human development and income inequality on suicide rates in 67 countries - Dela Cruz, Russel Matthew M.; Maguiguilid, Shaira Jane F.; Esguerra, Emmanuel F. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
Suicide remains to be a problem in both the developing and developed world. However intuitive though, previous studies have shown inconsistent results about the effects of income inequality on suicide. To see the differences in the effects of the variables across income levels and gender, this study pooled data from 67 countries from 2000_2015 and grouped them according to World Bank income classifications. This allowed the study to broaden perspectives on suicides in lower middle income countries. Moreover, we posit a shift of focus to outcome_related factors to explain the varying relationship of inequality and suicide. Using fixed_effects cross country panel data regressions, this study supports the notion that outcomes, represented by the human development index, affect suicide more than income alone. On average, income inequality and suicide appear to have an insignificant relationship although a weak negative relationship is found in upper middle income countries. Similar with previous studies, unemployment has a positive and significant relationship with suicide. But when comparing its effect within each income level, it only shows significance in low middle income countries. Contrary to previous research, this study also finds suicide to have no significant relationship with urbanization and industrialization. Lastly, the results of this study consistently find a significant and negative relationship between fertility and suicide.
Thesis (B.S. Economics) -- University of the Philippines Diliman
Keywords: Suicide victims -- Statistics; Income distribution; Economic development